Numerical simulation on convection of non-Newtonian fluid in a porous enclosure with non-uniform heating and thermal radiation - S. Sivasankaran; M. Bhuvaneswari; A.K. Alzahrani (Alexandria Engineering Journal, 2020)
The aim of the numerical simulation is to explore the laminar, incompressible, buoyant induced convection flow and heat transfer of Casson fluid in a porous square box in the presence of thermal radiation. Thermal insulation is imposed on horizontal walls. The vertical boundaries of the closed box are maintained with sinusoidal thermal distribution. The non-Darcy porous model is adopted in the present study along with Navier-Stokes equations. The solution is obtained by finite volume method with SIMPLE algorithm. The results are explored over a range of radiation parameter, Casson fluid parameter, and Darcy numbers. It is found that thermal stratification is found for higher values of Casson liquid parameter in the presence of radiation. The kinematic energy enhances on rising the values of Casson liquid parameter & radiation parameter. The heat transport deteriorates on growing the values of radiation parameter and it enhances on growing the Casson fluid parameter.